Complex and Multidimensional Lipid Raft Alterations in a Murine Model of Alzheimer's Disease. (10th August 2010) - Chadwick, Wayne; Brenneman, Randall; Martin, Bronwen; Maudsley, Stuart
Abstract : Various animal models of Alzheimer's disease (AD) have been created to assist our appreciation of AD pathophysiology, as well as aid development of novel therapeutic strategies. Despite the discovery of mutated proteins that predict the development of AD, there are likely to be many other proteins also involved in this disorder. Complex physiological processes are mediated by coherent interactions of clusters of functionally related proteins. Synaptic dysfunction is one of the hallmarks of AD. Synaptic proteins are organized into multiprotein complexes in high-density membrane structures, known as lipid rafts. These microdomains enable coherent clustering of synergistic signaling proteins. We have used mass analytical techniques and multiple bioinformatic approaches to better appreciate the intricate interactions of these multifunctional proteins in the 3xTgAD murine model of AD. Our results show that there are significant alterations in numerous receptor/cell signaling proteins in cortical lipid rafts isolated from 3xTgAD mice.